Polysaccharide-based hydrogels with tunable composition as 3D cell culture systems. Issue 4 (April 2018) - Gentilini, Roberta; Munarin, Fabiola; Bloise, Nora; Secchi, Eleonora; Visai, Livia; Tanzi, Maria Cristina; Petrini, Paola
Background: To date, cell cultures have been created either on 2-dimensional (2D) polystyrene surfaces or in 3-dimensional (3D) systems, which do not offer a controlled chemical composition, and which lack the soft environment encountered in vivo and the chemical stimuli that promote cell proliferation and allow complex cellular behavior. In this study, pectin-based hydrogels were developed and are proposed as versatile cell culture systems. Methods: Pectin-based hydrogels were produced by internally crosslinking pectin with calcium carbonate at different initial pH, aiming to control crosslinking kinetics and degree. Additionally, glucose and glutamine were added as additives, and their effects on the viscoelastic properties of the hydrogels and on cell viability were investigated. Results: Pectin hydrogels showed in high cell viability and shear-thinning behavior. Independently of hydrogel composition, an initial swelling was observed, followed by a low percentage of weight variation and a steady-state stage. The addition of glucose and glutamine to pectin-based hydrogels rendered higher cell viability up to 90%-98% after 1 hour of incubation, and these hydrogels were maintained for up to 7 days of culture, yet no effect on viscoelastic properties was detected. Conclusions: Pectin-based hydrogels that offer tunable composition were developed successfully. They are envisioned as synthetic extracellular matrix (ECM) either to study complex cellular behaviors or to be applied as tissue engineering substitutes.